2012
DOI: 10.1111/j.1651-2227.2011.02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes among Swedish children: the role of social capital in the family, school and neighbourhood

Abstract: Social capital in the family, school and neighbourhood matters for children's health and well-being and the contributions from each context seem to be additive. Besides the family context, investments for improving child health should primarily be in the school, focusing on social relations and on creating safe and cohesive school environments. Neighbourhood social capital is also of importance and so must be taken into consideration when planning child health promotion interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 22 publications
7
40
0
2
Order By: Relevance
“…Other studies, both from the Nordic countries and elsewhere, have shown that social capital in the family, at school and in the neighborhood has a positive influence on the children's health and wellbeing. [7,37,38,49] The study supports conclusions from other studies stating that a general economic growth is not enough for the wellbeing of the population. It also supports the importance of the social cohesion, affiliation and solidarity, advanced and reinforced by equal distribution of the wealth.…”
Section: Resultssupporting
confidence: 85%
“…Other studies, both from the Nordic countries and elsewhere, have shown that social capital in the family, at school and in the neighborhood has a positive influence on the children's health and wellbeing. [7,37,38,49] The study supports conclusions from other studies stating that a general economic growth is not enough for the wellbeing of the population. It also supports the importance of the social cohesion, affiliation and solidarity, advanced and reinforced by equal distribution of the wealth.…”
Section: Resultssupporting
confidence: 85%
“…The importance of good communication with parents for children’s well-being, including after a parental split-up, has been reported [37]. The importance of the family has been indicated in a study about social capital and children’s health, along with the effect of the school’s social capital on the children’s social well-being and on their subjective health complaints [38]. The results of this study on teachers’ support and participatory aspects related to a classroom situation also showed that supportive structures in the school organisation, along with good peer relationships, were strongly associated with the positive health of pupils.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three social capital milieux the one generated within the family was found to be the most substantial (Eriksson et al, 2012).…”
Section: The Impacts Of Social Assets On Childrenmentioning
confidence: 99%